2021
DOI: 10.1128/jvi.00010-21
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 Is a Receptor for Human Respiratory Syncytial Virus in Cotton Rats

Abstract: Respiratory syncytial virus (RSV) has been reported to use CX3CR1 in vitro as a receptor on cultured primary human airway epithelial cultures. To evaluate CX3CR1 as the receptor for RSV in vivo , we used the cotton rat animal model because of its high permissiveness for RSV infection. Sequencing the cotton rat CX3CR1 gene revealed 91% amino acid similarity to human CX3CR1. Previous work found that RSV binds to CX3CR1 via its attachment glycoprotein (G protein) to infect primary human ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Furthermore, it has been recently shown that cotton rats express CX3CR1 in their lungs that is very similar to the human equivalent (34). Importantly, it has also been shown that RSV infection of cotton rat lungs is dependent upon CX3CR1 further validating these animals as a model of human infection and for vaccine candidate testing (34).…”
Section: Immunization Protocolmentioning
confidence: 99%
“…Furthermore, it has been recently shown that cotton rats express CX3CR1 in their lungs that is very similar to the human equivalent (34). Importantly, it has also been shown that RSV infection of cotton rat lungs is dependent upon CX3CR1 further validating these animals as a model of human infection and for vaccine candidate testing (34).…”
Section: Immunization Protocolmentioning
confidence: 99%
“…Moreover, CRs can be used in maternal antibody studies, as RSV antibodies transfer from dames to pups via the placenta and breast milk [297][298][299][300]. Further, CX3CR1 is a receptor used by RSV for infection of CRs [301]. While the cotton rat model has been used to evaluate drugs and vaccines, limitations of this model include cost, procurement (i.e., limited suppliers), and lack of robust tools to evaluate immune responses.…”
Section: Cotton Ratmentioning
confidence: 99%
“…G protein mediating virus attachment; inhibiting IFN type I production; promoting Th2-polarized response. (Imai et al, 1997;Tripp et al, 2001;Harcourt et al, 2006;Chirkova et al, 2013;Chirkova et al, 2015;Jeong et al, 2015;Johnson et al, 2015;Zhivaki et al, 2017;Anderson et al, 2020;Green et al, 2021) Nucleolin F protein mediating virus internalization (Tayyari et al, 2011;Hegele, 2012;Griffiths et al, 2020;Mastrangelo et al, 2021) EGFR F protein inducing macropinocytosis of RSV; promoting virus fusion; increasing airway mucus secretion. (Currier et al, 2016;Lingemann et al, 2019) IGF1R F protein facilitating the translocation of nucleolin to cell membrane (Griffiths et al, 2020) HSPGs G protein virus attachment.…”
Section: Cx3cr1mentioning
confidence: 99%
“…The CX3CR1-CX3CL1 axis has been shown to play an important role in the pathogenesis of brain and neurodegenerative diseases, such as Alzheimer's disease (Lee et al, 2018), but its role in lung diseases, especially in infectious respiratory diseases, is poorly characterized. In RSV infection, the conserved CXC3 motif of its G glycoprotein was able to bind to CX3CR1 in vitro and in vivo to initiate infection (Jeong et al, 2015;Anderson et al, 2020;Green et al, 2021). Given its expression pattern in the lung, which matched the tropism of RSV infection, studies have shown that CX3CR1 is a more attractive candidate than HSPGs in vivo, since HSPGs are a primary receptor on immortalized cell lines but are expressed at much lower levels in the human airway epithelium, the primary site of RSV infection (Anderson et al, 1988;Johnson et al, 2015;Anderson et al, 2020;Green et al, 2021).…”
Section: Respiratory Syncytial Virus Receptors Cx3c Chemokine Receptormentioning
confidence: 99%
See 1 more Smart Citation